Chemical Properties of 15-year-old Teak (Tectona grandis L.f) from Different Seed Sources - Ganis Lukmandaru; Pormando Manalu; Tomy Listyanto; Denny Irawati; Rini Pujiarti; Fanny Hidayati; Dian Rodiana (Masyarakat Peneliti Kayu Indonesia, 2016)
Fifteen year-old teak wood samples planted in Ciamis FMU (Perhutani Enterprise) were evaluated for their chemical properties. Three seed sources such as conventional seed, clone, and superior wood and radial positions namely sapwood, outer heartwood, and inner heartwood were the observed factors. The specimens were taken from the bottom parts of their sources. Completely randomized design was used. Cell wall components were analyzed by various gravimetric methods.Analysis of variance and Duncan’s test were performed for data analysis. The results showed that no significant difference in the quantity of cell wall components (cellulose, hemicellulose, and lignin), extractives (ethanol-toluene and hot-water solubles), ash, and silica content among the seed sources. Superior teakwood or Jati Plus Perhutani, which has the highest growth rate (2.1 3.6 cm/year) among others, showed a comparative higher average pH values (7.08 7.38) and solubility in 1% NaOH (17.22 17.83%) than other sources. Radial factors significantly affected ethanol-toluene extractive and lignin content. The ethanol-toluene extractive had the highest content (9.30 11.54%) at the outer part of heartwood while lignin content was the lowest (28.12 30.10%) in the inner part. The result indicated some good characteristics of young teak trees compared to the mature ones in relation to wood processing.